PENGARUH KOMBINASI MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KENIKIR (Cosmos caudatus Kunth) SISTEM VERTIKULTUR - Randi Galih Prayugo; Aulia Rahmawati (Innofarm : Jurnal Inovasi Petanian, 2026)
Limited agricultural land in urban areas has encouraged the application of verticultures system as an efficient and environmentally friendly cultivation method. This study aimed to evaluate the effect of different growing media compositions on the growth and yield of kenikir (Cosmos caudatus Kunth.) The experiment was conducted from September to December 2025 in Karangbolong Village, Kebumen, using a non-factorial Randomized Complete Blok Design (RCBD) with four treatments: M1 (soil + compost + cocopeat), M2 ( soil + compost + rice husk charcoal), M3 (soil + compost + soil), and M4 (soil + compost + rice husk), each replicated six times. Data were analyzed using analysis of variance (ANOVA) followed by the Least Significant Difference (LSD) test at a 5% significance level. The results showed that most growth and yield parameters were not significantly from several others treatmenths. Overall, growing media composition influenced the physical and chemical properties of the media, affecting plant growth performance. Treatment M3 was considered the best combination as it consistently showed superior trends in several key parameters.